The impact of interpersonal relationships on mental health of Polish medical students - Piotr Limanówka; Julia Kuca; Julia Laska; Julia Łacwik; Aleksandra Szczuraszyk; Janusz Kasperczyk (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Interpersonal relations significantly impact our well-being and mental health. They are also crucial among students, especially when they start living independently in a new social environment. The study aimed to determine the impact of relations on the occurrence of depression, anxiety, and drowsiness among medical students in Poland. Material and methods: An online questionnaire was created, consisting of four parts: the authors' questionnaire on interpersonal relations, the Beck Depression Inventory (BDI), the Generalized Anxiety Disorder 7-item Scale (GAD-7), and the Epworth Sleepiness Scale (ESS). The results were analyzed using STATISTICA software. Results: 2339 completed questionnaires were obtained. 69.75% of the subjects had good/rather good relations with their co-tenants, and 5.04% - had bad/definitely bad. 85% of the participants had good relations with their parents. 65.63% of the respondents were satisfied with their social relationships; in addition, 71.91% of respondents were satisfied with their relationships with their friends. Poor relations with family and co-tenants, and poor social and friend relationships were linked to higher levels of depression, anxiety, and sleepiness. This phenomenon was particularly evident among introverts. Conclusions: Identifying the risk factors could significantly improve the prevention, diagnosis, and treatment of mental disorders in this group. Supporting students and paying greater attention to social competencies equally with medical knowledge acquired by them would be highly recommended.